2018
DOI: 10.1021/acs.iecr.8b00914
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid and Sulfuric Acid-Based Pretreatment of Bamboo: Biomass Delignification and Enzymatic Hydrolysis for the Production of Reducing Sugars

Abstract: The present work investigates the efficiency of two pretreatment pathways of biomass, namely ionic liquid (IL) and dilute sulfuric acid (H2SO4) hydrolysis. Both processes are compared in terms of their composition and enzymatic saccharification efficacy. For the IL process, bamboo was dissolved in 1-ethyl-3-methylimidazolium acetate ([Emim]­[OAc]) at different temperatures (90, 110, 130, and 150 °C) for 3 h. These pretreated bamboo samples were then characterized by thermogravimetric analysis and X-ray diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…The disappearance of hemicellulose peak after the HAc catalytic process is due to the high extent of hemicellulose removal during acid pretreatment, observations that agree with the literature. 22 The hemicellulose fraction in solid residues pretreated with PIL lessened, but most of the hemicellulose remained within the poplar, which was consistent with the compositional data. The pyrolysis residue of poplar decreased sharply when acid-IL was performed.…”
Section: Compositional and Structural Changes During Consolidated Processsupporting
confidence: 85%
See 1 more Smart Citation
“…The disappearance of hemicellulose peak after the HAc catalytic process is due to the high extent of hemicellulose removal during acid pretreatment, observations that agree with the literature. 22 The hemicellulose fraction in solid residues pretreated with PIL lessened, but most of the hemicellulose remained within the poplar, which was consistent with the compositional data. The pyrolysis residue of poplar decreased sharply when acid-IL was performed.…”
Section: Compositional and Structural Changes During Consolidated Processsupporting
confidence: 85%
“…Recently, Mohan et al reported the consolidated pretreatment of bamboo in H 2 SO 4 -[C 2 C 1 Im][OAc] (i.e., acid pretreatment followed by IL pretreatment) to understand the effect of the consolidated process on reducing sugars yield. 22 A glucose yield of 90% was achieved after enzymatic hydrolysis. However, a low solid loading (1.3 wt%) and a high enzyme loading (50 mg of cellulase (ATCC 26921) enzyme) were used, so the results may not be reflective of a more intensified process that would be required for a sustainable biorefinery.…”
Section: Individual Vs Consolidated Pretreatment and Saccharificationmentioning
confidence: 98%
“…Though some authors, e.g. Miao et al (2017) and Mohan et al (2018), state that [Emim][OAc] has high dissolution capacity over noncellulosic compounds, it should be borne in mind that the studies were done with pure [Emim] [OAc] whereas this work used a mixture of [Emim][OAc] and DMSO. Another possible reason for the complicated dissolution is the presence of lignin-carbohydrates complexes (Cheng et al 2011).…”
Section: Performance and Characteristics Of The Membranes Prepared DImentioning
confidence: 99%
“…DMSO, is usually added to the system, enhancing the solvent power of the IL by decreasing the time needed for dissolution even at lower temperatures (Isik et al 2014). Of the many solvents available, 1-ethyl-3-methylimidazolium acetate ([Emim][OAc]) is considered an optimal choice as it has relatively low viscosity, high dissolution power for cellulose (up to 20-30 wt.% depending on the temperature of the dissolution) and even higher dissolution power for lignin and hemicelluloses, due to their non-crystalline structure, and it can thus be utilized in dissolution of untreated lignocellulosic materials (Beckwith et al 2010;Mäki-Arvela et al 2010;Li et al 2011;Saha et al 2017;Mohan et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Biomass Reference 1-Ethyl-3-methylimidazolium acetate Bamboo, Hinoki Cypress wood, Sugarcane bagasse, Pine wood [81,82,83,84,85,86] Triethylammonium hydrogensulfate with 20 wt % water Miscanthus giganteus [68] Cholinium lysinate, Cholinium acetate Sorghum, Switchgrass, Eucalyptus, Pine [87,88,89] 1-Ethyl-3-methylimidazolium methanesulfonate Pine needles [90] 1-Butyl-3-methylimidazolium acetate Rice straw [91] 1-Ethyl-3-methylimidazolium acetate (42 wt. %) in DMSO Switchgrass [92] 1-Ethyl-3-methylimidazolium acetate, 1-Allyl-3-methylimidazolium formate and acetate…”
Section: Ionic Liquidmentioning
confidence: 99%